The perception of auditors on the role of accountants in social reporting and social responsibility / Aida Sharini Abdul Wahab - Abdul Wahab, Aida Sharini (Faculty of Accountancy, 1992)
The accounting profession is no more confined to only book keeping. It is a multi-disciplinary profession encompassing the traditional ^non-accounting' areas such as political, social, economic and environmental. The accountants therefore play an important role as well by being responsible for the society's interest and the public as a whole. Accountants are therefore expected to produce reports that are relevant, reliable and understandable and the auditors should ensure that the firms disclose not only their contributions to society, but also the costs incurred on society.